Adding Value to Trade Space Exploration When Designing Complex Engineered Systems. Issue 2 (31st May 2017) - Simpson, Timothy W.; Miller, Simon; Tibor, Elliott B.; Yukish, Michael A.; Stump, Gary; Kannan, Hanumanthrao; Mesmer, Bryan; Winer, Eliot H.; Bloebaum, Christina L.
ABSTRACT: Design decision‐making involves tradeoffs between many design variables and attributes, which can be difficult to model and capture in complex engineered systems. To choose the best design, the decision maker is often required to analyze many different combinations of these variables and attributes and process the information internally. Trade Space Exploration (TSE) tools, including interactive and multidimensional data visualization, can be used to aid in this process and provide designers with a means to make better decisions, particularly during the design of complex engineered systems that have multiple, competing objectives. In this paper, we investigate the use of TSE tools to support decision makers using a Value‐Driven Design (VDD) approach for complex engineered systems. A VDD approach necessitates a rethinking of TSE, and we outline and illustrate four different uses of a VDD approach to TSE. The research leverages existing TSE paradigms and multidimensional data visualization tools to identify optimal designs when using a value function for a system. A satellite design example is used to demonstrate the differences between a VDD approach to design complex engineered systems and a multiobjective approach to capture the Pareto frontier. Ongoing and future work is also discussed.